2015
DOI: 10.1017/ipm.2014.82
|View full text |Cite
|
Sign up to set email alerts
|

All of us? An exploration of the concept of mental health literacy based on young people’s responses to fictional mental health vignettes

Abstract: As mental health literacy is increasingly becoming a goal of mental health policy, it is timely that a shared understanding of this important concept is articulated. The current definition of mental health literacy is narrow in its focus on the recognition of mental disorders. A more broad-based definition of mental health literacy should be adopted by policy makers, reflecting the full range of determinants of mental health and recognising the importance of mental wellbeing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 13 publications
(10 reference statements)
0
12
0
Order By: Relevance
“…Although vignettes are recognised as powerful means of accessing valid, naturalistic responses (Chambers et al 2015), it is sometimes difficult to determine the extent to which data reflect the specific features of the vignettes provided, rather than more generalisable illness representations. For instance, although the name 'Morgan' was selected to represent a gender-neutral character, participants' responses indicated that it was more strongly associated with males, which influenced their inferences about the vignette target.…”
Section: Study Strengths and Limitationsmentioning
confidence: 99%
“…Although vignettes are recognised as powerful means of accessing valid, naturalistic responses (Chambers et al 2015), it is sometimes difficult to determine the extent to which data reflect the specific features of the vignettes provided, rather than more generalisable illness representations. For instance, although the name 'Morgan' was selected to represent a gender-neutral character, participants' responses indicated that it was more strongly associated with males, which influenced their inferences about the vignette target.…”
Section: Study Strengths and Limitationsmentioning
confidence: 99%
“…MHL has been conceptualized in different ways since the term was first coined by Jorm and colleagues in 1997 [ 6 , 8 10 ]. Traditionally, MHL and its measures have focused on knowledge and beliefs about mental -ill-health rather than on mental health [ 11 ]. However, in past years, MHL has evolved from a focus on mental -ill-health and risk factors to providing an asset for health that can be strengthened through educational initiatives [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…This period of transition in education from school to university represents a significant time for students (Thomas, 2012). A suggested strategy to improve (Ahead of Print) levels of help-seeking for mental health problems is to increase levels of mental health knowledge (Chambers, Murphy, & Keeley, 2015;Gulliver, Griffiths, & Christensen, 2010;Jorm, 2012). This includes knowledge of psychological difficulties, which aid their recognition, management and prevention and are critical for high performing athletes in third level education who are part of this high risk group (Rice et al, 2016).…”
mentioning
confidence: 99%